Spatial scene representations formed by self-organizing learning in a hippocampal extension of the ventral visual system. - Rolls, E; Tromans, J; Stringer, S (2008)
We show in a unifying computational approach that representations of spatial scenes can be formed by adding an additional self-organizing layer of processing beyond the inferior temporal visual cortex in the ventral visual stream without the introduction of new computational principles. The invariant representations of objects by neurons in the inferior temporal visual cortex can be modelled by a multilayer feature hierarchy network with feedforward convergence from stage to stage, and an associative learning rule with a short-term memory trace to capture the invariant statistical properties of objects as they transform over short time periods in the world. If an additional layer is added to this architecture, training now with whole scenes that consist of a set of objects in a given fixed spatial relation to each other results in neurons in the added layer that respond to one of the trained whole scenes but do not respond if the objects in the scene are rearranged to make a new scene from the same objects. The formation of these scene-specific representations in the added layer is related to the fact that in the inferior temporal cortex and, we show, in the VisNet model, the receptive fields of inferior temporal cortex neurons shrink and become asymmetric when multiple objects are present simultaneously in a natural scene. This reduced size and asymmetry of the receptive fields of inferior temporal cortex neurons also provides a solution to the representation of multiple objects, and their relative spatial positions, in complex natural scenes.